An investigation of barriers and enablers to advanced nursing roles in Australian general practice. Issue 2 (June 2015) - McKenna, Lisa; Halcomb, Elizabeth; Lane, Riki; Zwar, Nicholas; Russell, Grant
Summary Over the past decade, there has been substantial increase in nurses' roles in primary health care, particularly in general practice settings. Simultaneously, there has been an expansion of advanced roles for nurses across a range of clinical environments. This paper draws upon findings from a study that sought to develop a framework to support development of advanced nursing roles in general practice. It presents findings from one part of that study that explored barriers and facilitators to the development of these roles. Twenty-three key leaders from nursing, general practice and professional organisations participated in semi-structured interviews. Data were analysed using thematic analysis. A range of factors was identified as key to developing advanced roles in general practice. These included increasing awareness and attractiveness of practice nursing, health reform activities, practice limitations, education and professional development. Understanding complex systems and workforce issues is required to promote active intervention that can facilitate development of advanced nursing roles in Australian general practice.